Research in social movements, conflicts and change. Vol. 36 - Coy, Patrick G. (Research in social movements, conflicts and change,, 2013)
This latest volume in the august Research in Social Movements, Conflicts and Change series carries on a long tradition of featuring only the best data-driven and multi-method research upon which useful theory can be painstakingly built. Part one focuses on old and new media platforms and their intersections with mobilization issues, highlighting protest websites and the US Tea Party movement. Part two investigates the roles elites play in advancing movement campaigns for increased rights and decreased inequalities in the US and Peru. The third section spotlights best and worst practices in conflict transformation and peacebuilding ventures in Croatia and Israel/Palestine, while the fourth section interrogates the use of consensus building processes in Local Social Forums and in the Occupy Movement. Finally, on the 50th anniversary of the publication of Neil Smelsers A Theory of Collective Behavior, we close with a creative combining of Smelsers structural functionalist approach with social identity models for understanding crowd behaviors in the context of university party riots.